Genetic Diversity and Structure of Lolium Species Surveyed on Nuclear Simple Sequence Repeat and Cytoplasmic Markers - Guan, Xuanli; Yuyama, Nana; Stewart, Alan; Ding, Chenglong; Xu, Nengxiang; Kiyoshi, Takako; Cai, Hongwei (Frontiers in Plant Science, 2017)
To assess the genetic diversity and population structure of Lolium species, we used 32 nuclear simple sequence repeat (SSR) markers and 7 cytoplasmic gene markers to analyze a total of 357 individuals from 162 accessions of 9 Lolium species. This survey revealed a high level of polymorphism, with an average number of alleles per locus of 23.59 and 5.29 and an average PIC value of 0.83 and 0.54 for nuclear SSR markers and cytoplasmic gene markers, respectively. Analysis of molecular variance (AMOVA) revealed that 16.27% and 16.53% of the total variation was due to differences among species, with the remaining 56.35% and 83.47% due to differences within species and 27.39% and 0% due to differences within individuals in 32 nuclear SSR markers set and 6 chloroplast gene markers set, respectively. The 32 nuclear SSR markers detected three subpopulations among 357 individuals, whereas the 6 chloroplast gene markers revealed three subpopulations among 160 accessions in the STRUCTURE analysis. In the clustering analysis, the three inbred species clustered into a single group, whereas the outbreeding species were clearly divided, especially according to nuclear SSR markers. In addition, almost all L. multiflorum populations were clustered into group C4, which could be further divided into three subgroups, whereas L. perenne populations primarily clustered into two groups (C2 and C3), with a few lines that instead grouped with L. multiflorum (C4) or L. rigidum (C6). Together, these results will useful for the use of Lolium germplasm for improvement and increase the effectiveness of ryegrass breeding.